The theory of indicative planning : lectures given in the University of Manchester - Meade, J. E. (Manchester : Manchester U.P., 1970)
This volume comprise of lectures focused on the problems which arise in planning ahead in an economy that is developed, industrialised, free enterprise but with considerable element of State activity and intervention.
lje 13/12/18
Loan
Keywords: Economic policy; Economic development